Neuroinflammation in Parkinson's Disease - Putative Pathomechanisms and Targets for Disease-Modification. - Grotemeyer, Alexander; Mcfleder, Rhonda Leah; Wu, Jingjing; Wischhusen, Joerg; Ip, Chi Wang (Frontiers in Immunology, 2022)
Parkinson's disease (PD) is a progressive and debilitating chronic disease that affects more than six million people worldwide, with rising prevalence. The hallmarks of PD are motor deficits, the spreading of pathological α-synuclein clusters in the central nervous system, and neuroinflammatory processes. PD is treated symptomatically, as no causally-acting drug or procedure has been successfully established for clinical use. Various pathways contributing to dopaminergic neuron loss in PD have been investigated and described to interact with the innate and adaptive immune system. We discuss the possible contribution of interconnected pathways related to the immune response, focusing on the pathophysiology and neurodegeneration of PD. In addition, we provide an overview of clinical trials targeting neuroinflammation in PD.
EVALuna2:523126